A new Brazilian species of the genus Philothalpus Kraatz (Coleoptera: Staphylinidae) - Klemann-Junior, Louri; Barroso, Paulo Ricardo Ramires; Pereira, Luana De Fátima Baraúna; Asenjo, Angélico (Zootaxa, 2024)
A new species of the genus Philothalpus (Coleoptera: Staphylinidae: Staphylinini: Philothalpina), Philothalpus precious Klemann-Junior, Barroso, Pereira & Asenjo, sp. nov., is described from Amazonas state, northern Brazil. Major diagnostic features are illustrated and the species is included in the key to Philothalpus species.